2013
DOI: 10.1007/s00406-013-0476-2
|View full text |Cite
|
Sign up to set email alerts
|

SPOCK3, a risk gene for adult ADHD and personality disorders

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is the most frequent psychiatric disorder in children, where it displays a global prevalence of 5 %. In up to 50 % of the cases, ADHD may persist into adulthood (aADHD), where it is often comorbid with personality disorders. Due to a potentially heritable nature of this comorbidity, we hypothesized that their genetic framework may contain common risk-modifying genes. SPOCK3, a poorly characterized, putatively Ca(2+)-binding extracellular heparan/chondroitin sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Genome‐wide association studies (GWAS) [Neale et al, ; Lasky‐Su et al, ,; Lesch et al, ; Mick et al, ; Neale et al, ; Hinney et al, ; Stergiakouli et al, ; Ebejer et al, ; Yang et al, ; Weber et al, ; Sánchez‐Mora et al, ; Zayats et al, ] have revealed additional candidate genes (e.g., CDH13, SPOCK3, KCNC1, KCNIP1, KCNIP4), although these variants have not achieved genome‐wide significance [Franke et al, ; Neale et al, ; Hinney et al, ; Sánchez‐Mora et al, ]. The most consistent finding is the CDH13 gene, which has been implicated in two family‐based GWAS [Lasky‐Su et al, ; Neale et al, ] and two case‐control GWAS [Lesch et al, ; Neale et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome‐wide association studies (GWAS) [Neale et al, ; Lasky‐Su et al, ,; Lesch et al, ; Mick et al, ; Neale et al, ; Hinney et al, ; Stergiakouli et al, ; Ebejer et al, ; Yang et al, ; Weber et al, ; Sánchez‐Mora et al, ; Zayats et al, ] have revealed additional candidate genes (e.g., CDH13, SPOCK3, KCNC1, KCNIP1, KCNIP4), although these variants have not achieved genome‐wide significance [Franke et al, ; Neale et al, ; Hinney et al, ; Sánchez‐Mora et al, ]. The most consistent finding is the CDH13 gene, which has been implicated in two family‐based GWAS [Lasky‐Su et al, ; Neale et al, ] and two case‐control GWAS [Lesch et al, ; Neale et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…In our Spock3 -deficient mice, the corticostriatal information processing might also be altered, because their corticostriatal neuronal circuits were moderately impaired during brain development. Furthermore, a recent genome-wide association study raises the possibility that Spock3 might be an ADHD-related gene [41]. Because the Spock3- mutant mice exhibited no hyperactivity, these results together suggest that Spock3- mutant mice might be an animal model of attention deficit disorder, included in ADHD, in which carelessness but not hyperactivity is dominant [42].…”
Section: Discussionmentioning
confidence: 87%
“…One of these SNPs (rs10983304) associated with NEO-PI-R-neuroticism leads to alternative splicing (https://snpinfo.niehs.nih.gov/snpinfo/snpfunc.htm). Functional genetic variants resulting in post-transcriptional alternative splicing have been implicated for other aADHD, Bipolar Disorder, Autism-Spectrum-Disorder, and personality traits related genes (Sharp et al 2014;Waltes et al 2014;Weber et al 2014). These findings may indicate small pleiotropic effects of single ASTN2 variants conferring overlapping, respective contrasting risks for ADHD, comorbid disorders, and ADHD related adult personality traits.…”
Section: Discussionmentioning
confidence: 98%